Pengaruh Cita Rasa dan Kepuasan Konsumen terhadap Pembelian Ulang Mie Pangsit Apilin di Bireuen - Khairun Nisa; Fahrika Zahra; Natasya Biha; Munna Wirah; Thania Laura (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study looks into how customer happiness and taste affect Mie Pangsit Apilin's recurring business in Bireuen. The investigation was carried out at Mie Pangsit Apilin in Bireuen using a quantitative approach. Although the precise quantity is unknown, the population consists of all customers that bought Mie Pangsit Apilin goods in 2024. One hundred people participated in the study. The findings of the regression analysis show that hypothesis Ha1 is validated, suggesting that flavor influences repeat purchases to some extent. This is demonstrated by a significance value of 0.005 < 0.05 and tcount > ttable at a 5% significance level (2.884 > 1.660). Similarly, tcount > ttable (4.180 > 1.660) and a significance level of 0.000 < 0.05 corroborate hypothesis Ha2, which demonstrates that part of the relationship between customer satisfaction and repeat purchases is positive. Furthermore, hypothesis Ha3 is validated, showing that flavor and customer happiness work together to significantly influence repeat business at the same time. While the coefficient of determination (R2) of 0.490 indicates that 49% of the variance in repeat purchases can be explained by taste and customer satisfaction, with the remaining 51% influenced by factors not examined in this study, the correlation coefficient (R) of 0.700 shows a strong relationship between the independent variables and repeat purchases.